2003
DOI: 10.1111/j.0906-6705.2003.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P4501A1 polymorphisms in a Caucasian population with porphyria cutanea tarda

Abstract: Porphyria cutanea tarda (PCT) is the most frequent porphyria in humans. The familial type is in contrast to the sporadic type due to an inherited defect of the uroporphyrinogen-II-decarboxylase (URO-D) and both types need additional porphyrinogens to lead to the clinical manifestation of the disease. Various factors such as xenobiotics (i.e. polycyclic aromatic hydrocarbons), alcohol, hormones and viral liver infections (hepatitis B and C) are known to induce porphyria. Cytochrome p450 enzymes play a crucial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…Gardlo et al in Germany, also found no association of PCT with the CYP1A1*2A allele (25), but in contrast to our findings, reported an association between the *4 allele and PCT, which was statistically significant in type 2 cases (25). These CYP1A2*4 (previously known as m4) genotype and allele frequencies are compared in Table 3, showing comparable frequencies in controls but higher frequencies in PCT in the previous study.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Gardlo et al in Germany, also found no association of PCT with the CYP1A1*2A allele (25), but in contrast to our findings, reported an association between the *4 allele and PCT, which was statistically significant in type 2 cases (25). These CYP1A2*4 (previously known as m4) genotype and allele frequencies are compared in Table 3, showing comparable frequencies in controls but higher frequencies in PCT in the previous study.…”
Section: Discussioncontrasting
confidence: 84%
“…Patients with well documented PCT and matched, communitybased controls were studied for eight variants in cytochrome P450 genes including: CYP1A1*2A, *2C and *4; CYP1A2*1E/*1K; *1K; *1F; rs2069522; CYP2E1*5 and for GSTM1 and GSTT1 deletion variants (denoted as GSTM1 null and GSTT1 null, respectively), which are known or suspected to have functional effects on their respective enzymatic activities (16,(28)(29)(30)(31)(32)(33). As noted, the CYP1A2*1F and CYP1A1*4 variants have been associated previously with PCT (17,18,25). Associations of these variants with known susceptibility factors, including use of alcohol, tobacco or estrogen, infections with hepatitis C virus or HIV, and UROD and HFE mutations as well as sex and age of onset, were studied.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Cytochrome p450 enzymes metabolize drugs, hormones, and other compounds, including oxidation of uroporphyrinogen, which depletes the UROD substrate . They also metabolize alcohol, estrogen, and other chemicals associated with PCT (that may break down to form a UROD inhibitor) . Additionally, CYP1A2 p450 may directly inhibit UROD in hepatocytes; polymorphisms are linked to PCT …”
Section: Chronic Hepatic Porphyriasmentioning
confidence: 99%
“…PCT, the commonest chronic porphyria may be acquired (Type I, 80%) or inherited (Type II, 20%) as an autosomal dominant trait with low penetrance. PCT is associated with many risk factors such as haemochromatosis and certain polymorphisms in cytochromes (CYP1A2) and the transferrin receptor 1 gene (TFRC) mutations, hepatitis C and HIV infections, excess alcohol intake, and exposure to oestrogens in women [38][39][40][41][42][43]. PCT has also been reported in patients on haemodialysis for chronic renal failure [44].…”
Section: Clinical Presentation and Diagnosis Of Chronic Porphyriasmentioning
confidence: 99%